Experimental method replacement of the osteo-chondral defects of the large joints (first results) - G. A. Airapetov; N. V. Zagorodniy; A. A. Vorotnikov (Медицинский вестник Юга России, 2019)
Objective: to develop and offer an original method of treatment of bone and cartilage defects of hyaline cartilage on the example of the knee joint.Materials and Methods: a prospective study conducted on experimental animals (sheep) in an amount of 30 individuals, whose age was from 1.5 to 3 years, weight was from 20 to 30 kg. All individuals divided into 3 representative groups of 10 individuals, depending on the method of replenishment of the joint defect. In all groups, a full-thickness defect of the articular cartilage performed to a subchondral bone 4.5 mm in diameter on the loaded surface of the inner condyle of the thigh. Distinct bone-cartilage fragments examined visually, evaluating the nature of the edges of the articular cartilage defect, the condition of its blood filling, the depth of the defect, the degree of closure of the defect by the emerging fibrous-cartilaginous layer. The area of the defect of the subchondral plate studied morphologically using light microscopy.Results: The best results are shown in group 3, where the bone-cartilaginous defects are practically fully replaced macroscopically and microscopically managed to trace the architectonics of the newly formed hyaline-like tissue, which indicates good early results of the application of the described method.Conclusions: the proposed original method of treatment of bone and cartilage defects of the knee joint allowed to get good results in the early stages. It is necessary to further observe the behavior of the regenerate in all experimental groups.